(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
This research was carried out in the framework of the President of the Kyrgyz Republic Sooronbay Jeenbekov’s Decree as of January 11, 2019, No. 1 «On declaring 2019 the Year of Regional Development and Digitalization of the Country» and presented as a report at the III International Round Table “Biological and Food Security, Ecology and Modern Digital Technologies «in Bishkek, Kyrgyzstan, September 16–17, 2019. The article also reflects the decisions of this Roundtable regarding the creation of a smart region based on the Issyk-Kul Oblast